2015
DOI: 10.1186/s41016-015-0003-6
|View full text |Cite
|
Sign up to set email alerts
|

Brain gray matter volume changes associated with motor symptoms in patients with Parkinson’s disease

Abstract: Background: Parkinson's disease (PD) is a common neurodegenerative disease. Most studies have found that the histopathological lesion is not only localized at the extrapyramidal area (basal ganglia) but also at the cortex in PD patients. Voxel-based morphometry (VBM) based on the voxel as a unit is described for quantitative detection of density and volume of brain tissue. In this study, VBM was used to investigate the brain gray matter changes associated with motor symptoms in PD patients. Methods: Twelve out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Females also tend to report more nonmotor symptoms than males, including increased fatigue, apathy, cardiovascular symptoms, anhedonia, sensory dysfunction, constipation, sweating, and pain (Martinez-Martin et al, 2012;Solla et al, 2012). Across all patients with PD, neuroimaging studies show lower gray matter volume in the basal ganglia, motor cortex, and cerebellum and lower FA in the substantia nigra of PD patients compared with controls (Berman & Miller-Patterson, 2019;Geng, Li, & Zee, 2006;Kang et al, 2015;Zhang et al, 2015). In recent work by the ENIGMA-PD Working Group, individuals with PD (n = 2,367, M age = 63.4 ± 9.8, 36% females) showed widespread cortical thinning in parietal association areas, primary and supplementary motor areas, inferior temporal cortex, precuneus, and PCC, and smaller volumes in the bilateral putamen, hippocampus, amygdala and accumbens compared to healthy controls (n = 1,183, M age = 59.4 ± 12.3, 46% females) (Laansma, Bright, Al-Bachari, & Anderson, 2020), but sex-by-diagnosis interactions were not significant.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Females also tend to report more nonmotor symptoms than males, including increased fatigue, apathy, cardiovascular symptoms, anhedonia, sensory dysfunction, constipation, sweating, and pain (Martinez-Martin et al, 2012;Solla et al, 2012). Across all patients with PD, neuroimaging studies show lower gray matter volume in the basal ganglia, motor cortex, and cerebellum and lower FA in the substantia nigra of PD patients compared with controls (Berman & Miller-Patterson, 2019;Geng, Li, & Zee, 2006;Kang et al, 2015;Zhang et al, 2015). In recent work by the ENIGMA-PD Working Group, individuals with PD (n = 2,367, M age = 63.4 ± 9.8, 36% females) showed widespread cortical thinning in parietal association areas, primary and supplementary motor areas, inferior temporal cortex, precuneus, and PCC, and smaller volumes in the bilateral putamen, hippocampus, amygdala and accumbens compared to healthy controls (n = 1,183, M age = 59.4 ± 12.3, 46% females) (Laansma, Bright, Al-Bachari, & Anderson, 2020), but sex-by-diagnosis interactions were not significant.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…Despite the abovementioned sex differences in clinical presentation and symptom expression, few neuroimaging studies have compared brain metrics in males and females with PD. Across all patients with PD, neuroimaging investigations show abnormal gray matter integrity in the basal ganglia, motor cortex, and cerebellum and lower FA in the substantia nigra [Berman and Miller-Patterson, 2019;Geng et al, 2006;Kang et al, 2015;Zhang et al, 2015]. Recently, the ENIGMA Parkinson's Disease Working Group revealed widespread cortical thinning in parietal association areas, primary and supplementary motor areas, inferior temporal cortex, precuneus, and PCC, smaller volumes in the bilateral putamen, hippocampus, amygdala and accumbens, and a temporal impact on thalamic volume over the course of disease (larger to smaller) in PD compared to healthy controls [van der Werf et al,], but sex by diagnosis interactions were not significant.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…As shown in Tables 2 , 3 , the highest classification performance was 92.24% (specificity), 92.42% (sensitivity), 89.58% (accuracy), and 89.77% (AUC) for GM and 71.93% (specificity), 74.87% (sensitivity), 71.18% (accuracy), and 71.82% (AUC) for WM. Therefore, machine learning methods on GM have achieved better classification performance than those on WM, which has indicated that PD has a greater effect on the brain regions of GM than WM (Feldmann et al, 2010 ; Ji et al, 2010 ; Kang et al, 2015 ). As seen in Table 4 , ReliefF method achieved the best classification performance: 89.66% (sensitivity), 80.01% (specificity), 84.92% (accuracy), and 84.84% (AUC).…”
Section: Resultsmentioning
confidence: 99%